(untitled) (The Journal of Psychology and Sociology, 2016)
Based on the analysis of theoretical literature, the article discusses the concept of emotional competence as an important factor in the development of personality. Emotional competence has no single definition. In modern literature there are active discussions about the terms emotional intelligence and emotional competence. This article discusses the differences between them. The main components of emotional competence are allocated. Some thoughts on how to assess emotional competence, problems of use of evaluation tools are presented. This article discusses the possible prerequisites for the development of emotional competence, contributing to understanding of emotions. They affect to the child’s emotional functioning at all levels of development. For example, the impact of early childhood experiences of interaction with parents. The article also examines the impact of the environment that parents arrange during the child’s upbringing and the strategy of children’s behavior at different models of attachment. The article examines the relationship between emotional competence and academic performance of adolescents, the relationship of emotional competence with stress, mental health, suicidal thoughts, aggressiveness and unreasonable absence at school. Personal qualities of emotionally competent adolescents promote the use of effective strategies in solving problem situations. In conclusion are discussed prospects for further research emotional competence.